STARTEGI GURU DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN SELAMA PANDEMI COVID 19 - Salim, Qolbin; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Learning during the Covid 19 Pandemic that was carried out online could not be effective, so teachers had to have special strategies in increasing the effectiveness of learning. This study aims to determine the strategies, inhibiting factors and supporting factors of teachers in increasing the effectiveness of learning during the Covid-19 Pandemic Period in economics class X IPS Man Singkawang City. This research is a qualitative research. Data was collected by interviewing the economics teacher of Class X Social Sciences Man, Singkawang City. The results of this study indicate that the teacher's efforts to improve the effectiveness of online learning during the Covid 19 pandemic are by conducting receptive learning and using the inquiry method. The inhibiting factors are poor internet access, inadequate student learning facilities, limited student quota, differences in character and student absorption. Meanwhile, the supporting factor is the school's support during the online learning period by providing internet quota assistance to teachers and good cooperation between teachers and parents.